Responsiveness and Predictive Ability of the Chinese Version of the Action Research Arm Test in People with Cerebral Infarction. (7th October 2019) - Zhao, Jiang-Li; Zhang, Tao; Xu, Zhi-Qin; Ding, Ming-Hui; Leng, Yan; Bian, Rui-Hao; Mao, Yu-Rong; Huang, Dong-Feng
Abstract : Purpose. To detect the responsiveness and predictive ability of the Chinese version Action Research Arm Test (C-ARAT) in participants within the first 3 months after cerebral infarction. Methods. Ninety-seven individuals (75 men, mean age 59.87 ± 10.94 years) with a first cerebral infarction were enrolled in this study. The participants were evaluated by two outcome measures: C-ARAT and the Barthel Activities of Daily Living Index (BI) at five time points: 0D, 3W, 3M, 6M and 1Y after enrolment. The standardised response mean (SRM) and the Wilcoxon signed rank test were used to analyse responsiveness. Predictive validity was determined by using Spearman's rank correlation coefficients. The predicted performance of C-ARAT on activities of daily living (ADLs) was measured by linear regression model. Floor and ceiling effects were estimated by counting the proportion of subjects falling outside the 5% lower or upper boundary, respectively. Results. The C-ARAT showed moderate to large responsiveness in detecting changes over time (SRM = 0.58–0.84). The C-ARAT subscales showed small to large responsiveness (SRM = 0.44–0.90). The C-ARAT at 0D showed moderate to good correlation with the BI scores at 3W, 3M and 6M (ρ  = 0.561–0.624, p < 0.001 ), and exhibited fair correlation with the BI score 1Y after enrolment (ρ  = 0.384, p < 0.05 ). C-ARAT was a good predictor (adjustedR 2  = 0.185–0.249) of BI within 3M follow-up. The C-ARAT total score showed a notable floor effect at 0D and 3W and a notable ceiling effect at 3M, 6M and 1Y. Conclusion. The results of this study support the use of the C-ARAT as a measurement of upper extremity function in individuals with a first cerebral infarction.